Perchlorates on Mars enhance the bacteriocidal effects of UV light - Jennifer Wadsworth (Nature Portfolio, 2017)
Abstract Perchlorates have been identified on the surface of Mars. This has prompted speculation of what their influence would be on habitability. We show that when irradiated with a simulated Martian UV flux, perchlorates become bacteriocidal. At concentrations associated with Martian surface regolith, vegetative cells of Bacillus subtilis in Martian analogue environments lost viability within minutes. Two other components of the Martian surface, iron oxides and hydrogen peroxide, act in synergy with irradiated perchlorates to cause a 10.8-fold increase in cell death when compared to cells exposed to UV radiation after 60 seconds of exposure. These data show that the combined effects of at least three components of the Martian surface, activated by surface photochemistry, render the present-day surface more uninhabitable than previously thought, and demonstrate the low probability of survival of biological contaminants released from robotic and human exploration missions.